Detección de grupos funcionales asociados a la rizosfera del cultivo de papa (Solanum tuberosum), en la localidad de Pastocalle, Cantón Latacunga, Provincia de Cotopaxi. - Mena Tipán, María José (2021)
This research was carried out in the Pastocalle Parish, Cantón Latacunga, and aimed to determine the total microbiota and detect the presence of functional groups such as nitrogen-fixing bacteria, fungi, and actinomycetes associated with the potato rhizosphere through laboratory prospecting. In soil, in root maceration and root fragments in two repetitions, where CFU*gr-1 and conidia*gr-1 were determined, for which we used specific culture media for each group, and the observations were made employing solutions of 10-7. Moreover, the microorganisms present in the repetitions and the sowing methods were compared from the colonies' data in the culture media. It was determined that there is the presence of 2.48*108 CFU*gr-1 in the first repetition performed and 2.67*108 CFU*gr-1 in the second repetition of microbiota full; Regarding the incidence of colonies in functional groups, 1.89*108 CFU*gr-1 of nitrogen-fixing bacteria, 3*108 CFU*gr-1 of fungi and 4.87*108 CFU*gr were obtained. -1 of actinomycetes from the sowing method by root maceration. Regarding the incidence of the same by the method of sowing by root fragments, 3.29*10 was obtained 8 CFU*gr-1 of nitrogen-fixing bacteria, 3.4*108 CFU*gr-1 of fungi, and 4.61*108 CFU*gr-1 of actinomycetes. The conidia count of each of the functional groups and total microbiota was performed, of which 1.19*108 conidia*gr-1 and 74.8*108 conidia*gr of total microbiota of the first were identified. and second repetition; Regarding the incidence of functional groups, it was found 1.46*108 conidia*gr-1 of nitrogen-fixing bacteria, 2.75*108 conidia*gr-1 of fungi and 2.14*108 conidia*gr-1 of actinomycetes by the root maceration method and 1.12*1010 conidia*gr-1 of nitrogen-fixing bacteria, 1.29*1010 conidia*gr-1 of fungi and 1.81*1010 conidia*gr of actinomycetes by root fragment method.